Spatial variations of rain intensity over a short length propagation for 5G links based on a rain gauge network - M. Rashid; Jafri Din; Omar Abdul Aziz (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Millimeter-wave (mm-wave) frequency range is among operating bands designated for terrestrial 5G networks. A critical challenge of link-budgeting in mm-wave 5G networks is the precise estimation of rain attenuation for short-path links. The difficulties are further amplified in tropical and subtropical regions where the rainfall rate has a higher intensity. Different models have been proposed to predict rain attenuation. The distance factor is an important parameter in predicting total attenuation from specific rain attenuation. This study investigates the distance factor based on rain gauge networks and measured rain attenuation at 26 GHz for a 300 m link in Malaysia. Considerable discrepancies between available models were observed especially when applied for shorter path links. Also, significant variability of rain intensity is observed from the rain gauge network. This study recommends further investigation of the distance factor for a shorter link. Hence, a measurement campaign incorporating rain gauge networks was established to examine spatial variations of rain intensity over a less than 1 km link. The motivation is to develop a suitable distance factor model for 5G mm-wave propagation.